High-resolution magnetostratigraphic records of the pliocene sedimentary successions in Yengisar section, NW China, and its tectonic implications - Zhou, Zaizheng; Pei, Junling; Li, Jianfeng; Cai, Yuhang; Hou, Lifu (Frontiers in Earth Science, 2022)
The Neogene strata upward-coarsening sandstone and conglomerate sequences at the periphery of the Northeastern Pamir record the neoid intense uplift of the paleosurface of the building mountains. To further improve our knowledge of source-sink processes, a detailed magnetostratigraphic investigation was carried out along the Yengisar section, which is located at the southwestern margin of the Tarim Basin. The new high-resolution magnetostratigraphic data revealed that the Artux Formation was deposited from 4.9 Ma to1.9 Ma with three sedimentation rates changes. The variations in sedimentation rate may be due to the pulsating exhumation of the Western Kunlun Mountain, caused by the northward motion of the Pamir salient. By integrating the evidences from the seismic reflection profile and other magnetostratigraphic investigations in this region, the basal age of the Xiyu Formation and the early stages of growth strata deposition were estimated at ~1.9 and 1.45 Ma, respectively.